Kontribusi Kepemimpinan Transformasional Kepala Sekolah, Kompetensi Profesional dan Komitmen terhadap Kinerja Guru Bk SMA/SMK di Kalimantan Tengah - Veronica Octadewi Taradifa; Ahmad Suriansyah; Sulistyana Sulistyana (LP. Ma'arif Janggan Magetan, 2024)
The performance of Guidance and Counseling (BK) teachers is evaluated based on the quality standards of the services they provide to optimally serve students in line with their duties and responsibilities. School principals must be able to guide, motivate, foster, and support BK teachers' services through transformational leadership to develop the potential of BK teacher resources. The performance of BK teachers is also supported by their professional competence and commitment, ensuring their performance meets service quality standards. This study aims to analyze the direct and indirect effects of transformational leadership by school principals, professional competence, and commitment on the performance of BK teachers in high schools and vocational schools in Central Kalimantan. The research is quantitative, using descriptive methods and correlation research techniques. The study population consists of 176 BK teachers, with 123 respondents selected using proportional random sampling techniques. Data collection involved questionnaires, and data analysis included descriptive analysis, classical assumption tests, multiple regression analysis, and path analysis. The results show that the regression coefficient of transformational leadership by school principals on BK teacher performance (X1-Y) is 0.485, the regression coefficient of professional competence on BK teacher performance (X2-Y) is 0.659, the regression coefficient of commitment on BK teacher performance (Z-Y) is 0.578, the regression coefficient of transformational leadership by school principals on commitment (X1-Z) is 0.634, the regression coefficient of professional competence on commitment (X2-Z) is 0.635, the regression coefficient of transformational leadership by school principals through commitment on BK teacher performance (X1-Z-Y) is 0.366, and the regression coefficient of professional competence through commitment on BK teacher performance (X2-Z-Y) is 0.367. The conclusion of this study is that there are significant direct effects of transformational leadership by school principals, professional competence, and commitment on the performance of BK teachers in high schools and vocational schools in Central Kalimantan. Additionally, there are significant indirect effects of transformational leadership by school principals and professional competence through commitment on the performance of BK teachers in Central Kalimantan. The recommendation for school principals is to support BK teachers in enhancing their professional competence through activities like MGBK, webinars, IHT, and independent training without neglecting their duties and responsibilities.